The Bilbao Group as a Model of Transculturalism and Hybrid Identity - Regueiro Salgado, Begoña (Madrygal. Revista de Estudios Gallegos, 2015)
After reviewing what critics have already said about the identity and the configuration of the Bilbao Group, this article offers a new proposal taking into account the new theories on transculturality and hybrid identities. Thus, the article proposes to apply these theories to find a link among the writers belonging to the Bilbao Group in a hybrid identity formed by Galician and Madrilenian cultural elements.
Keywords: Bilbao Group; madrigalegos; hybridization; transculturalism; identity